VARICOCELE IN ADOLESCENTS AND MEN OF REPRODUCTIVE AGE: CHALLENGES OF EARLY DETECTION AND PREVENTION (International journal of medical sciences, 2026)
Varicocele represents one of the most prevalent correctable causes of male infertility and is particularly significant in adolescents and men of reproductive age. Characterized by abnormal dilation and tortuosity of the pampiniform venous plexus, varicocele is detected in approximately 15% of the general male population and in up to 35–40% of men presenting with primary infertility. In adolescents, its prevalence ranges from 10% to 20%, increasing with pubertal progression. Despite its high frequency, early detection remains suboptimal due to asymptomatic presentation, social stigma, limited awareness, and variability in screening practices. Pathophysiologically, varicocele contributes to impaired spermatogenesis through scrotal hyperthermia, hypoxia, oxidative stress, hormonal imbalance, and venous reflux. These mechanisms may result in testicular hypotrophy, reduced semen quality, and long-term reproductive dysfunction. Early diagnosis during adolescence is controversial, as not all cases progress to infertility; however, delayed intervention may lead to irreversible testicular damage. Preventive strategies include structured screening programs, standardized ultrasonographic criteria, public health education, and individualized risk stratification. This review synthesizes current scientific evidence regarding epidemiology, pathophysiology, diagnostic modalities, and preventive approaches. Emphasis is placed on balancing overtreatment and undertreatment while promoting evidence-based clinical decision-making. Early identification combined with appropriate monitoring and timely intervention may reduce future infertility burden and improve reproductive health outcomes in affected populations.